ANALISIS TIMBULAN, KOMPOSISI DAN ARAHAN PENGELOLAAN SAMPAH DI KECAMATAN PELAIHARI KABUPATEN TANAH LAUT - Yustina Yustina; Suyanto Suyanto; Rizqi Puteri Mahyudin; Leila Ariyani Sofia (EnviroScienteae, 2021)
High urban population growth and increasing development activities in various sectors cause various problems in urban areas, one of which is the problem of waste in addition to other problems, such as urbanization, slum settlements, and so on. The problem of urban waste arises because of poor waste management. Therefore, this research is expected to be able to find out the availability of waste handling facilities and infrastructure in Pelaihari District so that it can overcome the waste that has not been transported based on the results of generation calculations and waste composition data. The purpose of the study was to analyze waste management, the amount of generation and composition of waste in Pelaihari District. The research method is descriptive quantitative. Analysis of household waste generation and composition refers to SNI 19-3964-1994. The average volume of waste generated by the sampling in Pelaihari District is 2.505 liters/person/day while the average weight of waste is 0.36 kilograms/person/day. The composition of the waste is dominated by organic waste (55%) then the most dry waste produced is plastic at 14%.